Partial Characterization of R-Plasmids from Pasteurella multocida Isolated from Turkeys - Berman, Stephen M. (1978)
Pasteurella multocida, isolated from turkeys during an outbreak of septicemic disease (“fowl cholera”), was found to be resistant to tetracycline, streptomycin, and sulfonamides. Agarose gel electrophoretic analysis of DNA from these isolates indicated the presence of extrachromosomal elements. Plasmid DNA was isolated by cesium chloride-ethidium bromide density centrifugation. Escherichia coli was transformed to antimicrobic resistance with this DNA. Two plasmids were isolated. One of these plasmids had a buoyant density of 1.7158 g/cm(3) (56.9 mol% guanine plus cytosine) and a molecular weight of 4.4 × 10(6) and conferred resistance to tetracycline, streptomycin, and sulfonamides. The other, having a buoyant density of 1.7198 g/cm(3) (61 mol% guanine plus cytosine) and a molecular weight of 3.44 × 10(6), conferred resistance to streptomycin and sulfonamides. Streptomycin resistance was mediated by streptomycin phosphotransferase. Compatibility group testing indicated that neither plasmid belonged to any of 13 compatibility groups (of conjugal plasmids). Both plasmids were also found to be compatible with three small, nonconjugative resistance plasmids.